2018
DOI: 10.3126/ijssm.v5i3.20602
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practices Regarding Hepatitis C Prevention among People of Rural Community, Lahore

Abstract: Introduction: Hepatitis C infection is developing risk and real burden on general wellbeing, overall prevalence of hepatitis C is 3% (170 million tainted individuals). Roughly 10 million individuals are contaminated in Pakistan and prevalence is relied upon to be higher in isolated places. Methodology: This was descriptive cross-sectional study. Convenient sampling was used and data was analyzed by SPSS version 21. Results: The findings of the research were good Response rate of this review was 100 % and mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“… 26 Findings of another study in Lahore, Pakistan, showed that 52% of their general public respondents believed that it is safe to deal and sit with patients infected with HCV. 27 More than half of the participants in our study agreed that people with a hepatitis virus should not work in restaurants and cafeterias and this was associated ( P = .009) with marital status. This was similar to a study that surveyed Al Jouf dentists showing that 32 (78%) of the participants agreed that people with a hepatitis virus should not work in restaurants and cafeterias.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“… 26 Findings of another study in Lahore, Pakistan, showed that 52% of their general public respondents believed that it is safe to deal and sit with patients infected with HCV. 27 More than half of the participants in our study agreed that people with a hepatitis virus should not work in restaurants and cafeterias and this was associated ( P = .009) with marital status. This was similar to a study that surveyed Al Jouf dentists showing that 32 (78%) of the participants agreed that people with a hepatitis virus should not work in restaurants and cafeterias.…”
Section: Discussionmentioning
confidence: 67%
“…This is akin to other studies conducted in Pakistan and Iraq. 27 , 29 , 33 The percentage of participants in this study who chose “always” in responding to sharing personal items (clothes, towels, toothbrush, and earphones) with others was 71 (12.9%) and “rarely” was 94 (17.1%). This is contradictory to the findings of the study conducted in Karachi which could be attributed to the increased level of knowledge among the participants in Karachi.…”
Section: Discussionmentioning
confidence: 89%
“…The need to apply special measures and laws in this area is becoming more noticeable (14). Medical centers such as hospitals, medical clinics, health centers and pharmacies are the most accessible treatment centers in the community (15) It is crucial to prioritize the mental health of medical center staff who are in direct contact with patients and bear the burden of a sensitive work position (16). Pharmacies are one of the most important health centers due to their direct interaction with people and the provision of medical services, pharmaceutical products, and hygiene and cosmetic products (17).…”
Section: Discussionmentioning
confidence: 99%
“…This knowledge gap contributes to the continued prevalence of hepatitis, as individuals may unknowingly engage in behaviors that put them at risk of contracting or spreading the virus. Addressing this issue necessitates comprehensive educational campaigns and targeted interventions aimed at increasing awareness about the modes of transmission, thereby empowering individuals to make informed decisions and take necessary precautions to prevent the spread of hepatitis [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%